Prevalence, risk factors, and treatment methods of thirst in critically ill patients: A systematic review and meta-analysis. - Takuto Fukunaga; Akira Ouchi; Gen Aikawa; Saiko Okamoto; Shogo Uno; Hideaki Sakuramoto (PLoS ONE)
Critically ill patients admitted to the intensive care unit (ICU) experience various symptoms and discomfort. Although thirst is a typical distressing symptom and should be assessed daily, it is crucial to understand its prevalence and risk factors in the ICU setting. Nevertheless, currently, systematic reviews of prevalence and risk factors are lacking. This study evaluated the prevalence and risk factors of thirst in critically ill patients. We conducted a comprehensive search of the MEDLINE, Cochrane Library, and CINAHL databases. The study design included cohort, cross-sectional, and intervention studies, including randomized and non-randomized controlled trials with control groups. The point estimates from each study were combined using a random-effects meta-analysis model. We aggregated the prevalence of thirst in ICU patients and calculated the point estimates and 95% confidence intervals. The risk of bias was assessed using the Cochrane Risk of Bias 2 tool and Newcastle-Ottawa Scale. Fifteen studies were eligible for inclusion, of which seven reported the prevalence of thirst. A total of 2,204 patients were combined, with a prevalence estimate of 0.70. The risk factors for thirst were categorized as patient and treatment factors: four patient factors (e.g., serum sodium concentration and severity of illness) and six treatment factors (e.g., nil per os and use of diuretics) were identified. However, the results showed high heterogeneity in the prevalence of thirst among critically ill patients. It was established that 70% of critically ill patients experienced thirst. Additional investigations are required to obtain a more comprehensive overview of thirst among these patients. Systematic review registration number The protocol was registered in PROSPERO (ID: CRD42023428619) on June 6, 2023. (URL: https://www.crd.york.ac.uk).